Interatomic Coulombic electron capture in atomic, molecular, and quantum dot systems - Bande, Annika; Pont, Federico M.; Gokhberg, Kirill; Cederbaum, Lorenz S. (Atmospheric monitoring for high energy astroparticle detectors (AtmoHEAD 2014), 2015)
The interatomic Coulombic electron capture (ICEC) process has recently been predicted theoretically for clusters of atoms and molecules. For an atom A capturing an electron e(ε) it competes with the well known photorecombination, because in an environment of neutral or anionic neighboring atoms B, A can transfer its excess energy in the ultrafast ICEC process to B which is then ionized. The cross section for e(ε) + A + B → A− + B+ + e(ε′) has been obtained in an asymptotic approximation based on scattering theory for several clusters [1,2]. It was found that ICEC starts dominating the PR for distances among participating species of nanometers and lower. Therefore, we believe that the ICEC process might be of importance in the atmosphere, in biological systems, plasmas, or in nanostructured materials. As an example for the latter, ICEC has been investigated by means of electron dynamics in a model potential for semiconductor double quantum dots (QDs) [3]. In the simplest case one QD captures an electron while the outgoing electron is emitted from the other. The reaction probability for this process was found to be relatively large.